On a Class of Nonlocal p(x)-Laplacian Neumann Problems: Mostafa Allaoui, Abdelrachid El Amrouss, Anass Ourraoui - Team, Support (Thai Journal of Mathematics, 2017)
This paper is aiming at obtaining weak solutions for a kirchhoff problem involving p(x)-Laplacian operator. The notion of Sobolev space with a variable exponent with combined conditions of nonlinearities lead us to generalize the case of p-kirchhoff problem where p is constant.